2021
DOI: 10.3390/cancers13102383
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Lamin A/C Does Not Facilitate Cancer Cell Transendothelial Migration but Compromises Lung Metastasis

Abstract: The mechanisms by which the nuclear lamina of tumor cells influences tumor growth and migration are highly disputed. Lamin A and its variant lamin C are key lamina proteins that control nucleus stiffness and chromatin conformation. Downregulation of lamin A/C in two prototypic metastatic lines, B16F10 melanoma and E0771 breast carcinoma, facilitated cell squeezing through rigid pores, and reduced heterochromatin content. Surprisingly, both lamin A/C knockdown cells grew poorly in 3D spheroids within soft agar,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…Immediately after the sacrifice, mice were transcardially perfused with PBS and the lungs were inflated via the trachea with low-gelling agarose (Cat. A9045, Sigma-Aldrich), fixed with paraformaldehyde (4% in PBS) for 2 h, dehydrated, and cleared using ethyl cinnamate as described ( 40 , 41 ). Cleared lung lobes were imaged in an Ultramicroscope II (LaVision BioTec) operated by the ImspectorPro software (LaVision BioTec, Bielefeld, Germany) as described ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after the sacrifice, mice were transcardially perfused with PBS and the lungs were inflated via the trachea with low-gelling agarose (Cat. A9045, Sigma-Aldrich), fixed with paraformaldehyde (4% in PBS) for 2 h, dehydrated, and cleared using ethyl cinnamate as described ( 40 , 41 ). Cleared lung lobes were imaged in an Ultramicroscope II (LaVision BioTec) operated by the ImspectorPro software (LaVision BioTec, Bielefeld, Germany) as described ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic interaction of the nucleus with the actomyosin cytoskeleton is required to ensure proper nuclear deformation to successfully squeeze the cell through small but not through large constrictions [ 52 , 53 ]. We have recently shown that nucleus deformation is the rate-limiting step for Β16F10 to pass through constrictions smaller than the nucleus [ 39 ]. Since ZMP-treated Β16F10 cells failed to cross large pores, these results suggest that interference with MT disassembly blocks the chemotaxis and haptotaxis of these cells at a distinct step, possibly prior to actomyosin-driven nuclear deformation.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cell TEM in vitro involves sequential steps ( Figure 2a ): spreading over the EC surface, protrusion through paracellular EC junctions, generation of a stable subendothelial pseudopodia that displaces the EC attachments to the endothelial-deposited ECM (basement membrane) and nucleus squeezing below the endothelial monolayer [ 39 ] ( Figure 2b and Videos 3 and 4). As expected, interference with actin turnover using Jasp blocked tumor TEM by abolishing the ability of Β16F10 cells to initially spread over the EC monolayer ( Figure 2c ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, PME-1 physically associates with the nuclear lamina (NL) ([37] and Figure S4A,B) and regulates phosphorylation of lamins, key structural components of the NL, but also other related proteins such as LAP2A/B that connect the NL to chromatin (Figure S4C). It has previously been shown that NL directly influences chromatin architecture [38, 39], and that de-regulation of the NL can lead to DNA damage and cell death, limiting both cancer cell growth in soft agar and metastasis [38, 40, 41]. Therefore, we next assessed whether PME-1 inhibition could alter nuclear structure and stability.…”
Section: Resultsmentioning
confidence: 99%